'Useless approvals'. Italian bicameralism and its decisional capacity. Issue 4 (1st October 2020) - Pedrazzani, Andrea; Zucchini, Francesco
ABSTRACT: In bicameral parliaments, upper chambers amend the bills that have been passed by lower chambers, and sometimes bills that are passed in one chamber never become law and just 'die' in the other. Why does one chamber fail or refuse to anticipate what the other will do? What can lead the political actors in one chamber to 'waste' their time and resources on a bill that will be never approved as law? How can we explain the variations in the number of such 'useless' approvals? This article helps answer these questions by focusing on 'useless approvals' in the Italian parliament (1979–2018). Italy offers an ideal setting to analyse this phenomenon, with two houses holding the same powers but characterised by varying degrees of political incongruence over time. We found that differences in preference between the two chambers positively affect the chances of useless approvals, above all for private members' bills.